Identification of the new HLA‐DQA1*01:15N allele in an Italian patient. (26th March 2017) - Battarra, M.; Condello, R.; Testi, M.; Stellitano, C.; Andreani, M.
Abstract : The novel allele DQA1*01:15N differs from DQA1*01:03:01:01 by 1 nucleotide substitutions in exon 2.